To simplify \( \frac{6^8}{6^3} \), you can use the property of exponents that states \( \frac{a^m}{a^n} = a^{m-n} \).
Applying this property, we get:
\[ \frac{6^8}{6^3} = 6^{8-3} = 6^5. \]
So, the simplified form is \( 6^5 \).
6^8/6^3
13 answers
To simplify \( \frac{6^8}{6^3} \), you can use the property of exponents that states \( \frac{a^m}{a^n} = a^{m-n} \).
Applying this property, we get:
\[ \frac{6^8}{6^3} = 6^{8-3} = 6^5. \]
So, the simplified form is \( 6^5 \).
To simplify \( \frac{3^5}{3} \), you can use the property of exponents that states \( \frac{a^m}{a^n} = a^{m-n} \).
Applying this property, we have:
\[ \frac{3^5}{3} = \frac{3^5}{3^1} = 3^{5-1} = 3^4. \]
Thus, the simplified form is \( 3^4 \).
To simplify \( (2^2)^5 \), you can use the property of exponents that states \( (a^m)^n = a^{m \cdot n} \).
Applying this property, we get:
\[ (2^2)^5 = 2^{2 \cdot 5} = 2^{10}. \]
So, the simplified form is \( 2^{10} \).
To simplify \( (5^4)^3 \), you can use the property of exponents that states \( (a^m)^n = a^{m \cdot n} \).
Applying this property, we have:
\[ (5^4)^3 = 5^{4 \cdot 3} = 5^{12}. \]
So, the simplified form is \( 5^{12} \).
To simplify \( (2^4)^5 \), you can use the property of exponents that states \( (a^m)^n = a^{m \cdot n} \).
Applying this property, we have:
\[ (2^4)^5 = 2^{4 \cdot 5} = 2^{20}. \]
So, the simplified form is \( 2^{20} \).
To simplify \( 6^4 \cdot 6^5 \), you can use the property of exponents that states \( a^m \cdot a^n = a^{m+n} \).
Applying this property, we get:
\[ 6^4 \cdot 6^5 = 6^{4+5} = 6^9. \]
So, the simplified form is \( 6^9 \).
No problem! To simplify \( 6^4 \cdot 6^3 \), you can use the property of exponents that states \( a^m \cdot a^n = a^{m+n} \).
Applying this property, we have:
\[ 6^4 \cdot 6^3 = 6^{4+3} = 6^7. \]
So, the simplified form is \( 6^7 \).